ANALISIS MANAJEMEN PEMBELAJARAN DALAM PENYELENGGARAAN PELATIHAN SERTA IMPLIKASINYA BAGI MUTU PROGRAM DI BPSDMD JAWA TENGAH - Handayani Agustina; Indra Simanungkalit (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze learning management and the learning environment in the implementation of Civil Servant (ASN) training programs and their implications for program quality at the Regional Human Resource Development Agency (BPSDMD) of Central Java Province. Method: This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving seven informants, including representatives from the Competency Certification and Quality Assurance Division, training managers, trainers (widyaiswara), and training participants. Data were analyzed using source triangulation. Results: The findings show that learning management has been implemented effectively through training needs identification using the SIJARI AKPK application, curriculum development, learning implementation through the SIPTENAN Learning Management System (LMS), and monitoring and evaluation activities. The learning environment generally supports the training process through adequate facilities and positive learning interactions. However, several challenges remain, including non-position-based training needs identification, low participation in online learning, internet connectivity issues, and limited learning resources. Novelty: This study integrates learning management and learning environment perspectives within the context of civil servant training and highlights their contribution to improving training program quality.